CORPORATE CRIMINAL LIABILITY FOR SUBSTANDARD WAGE VIOLATIONS: A CASE STUDY OF PT. SAHABAT LINGKUNGAN HIDUP - Khrisnu Wahyuono (jfpublisher, 2025)
This study examines the enforcement of corporate criminal liability for labor law violations in Indonesia through an in-depth qualitative case study of PT. Sahabat Lingkungan Hidup. Despite Indonesia’s comprehensive legal framework guaranteeing minimum wages, employment security, and social protection, findings reveal persistent and deliberate non-compliance by the company, including underpayment of wages, denial of overtime and annual leave, misclassification of workers, and non-enrollment in social security programs. Data collected from legal documents, interviews, and field observations demonstrate that institutional fragmentation, limited enforcement capacity, and bureaucratic inaction have rendered existing sanctions ineffective. The analysis integrates labor protection theory, the enforcement pyramid model, and political economy perspectives to explain how weak state capacity and overlapping jurisdictions sustain a culture of impunity. The study concludes that legislative reforms—such as the Job Creation Law—remain insufficient without stronger institutional coordination, adequate resources, and political commitment. Strengthening inspectorate capacity, enhancing inter-agency collaboration, and prioritizing labor rights enforcement are essential to transforming Indonesia’s formal labor protections into meaningful workplace realities.